China and the first Vietnam War, 1947-54 - Calkins, Laura M. (Laura Marie) (Routledge studies in the modern history of Asia (2005), 2013)
"Charts the development of the first Vietnam War--the war between the Vietnamese Communists (the Vietminh) and the French colonial power--considering especially how relations between the Vietminh and the Chinese Communists had a profound impact on the course of the war. It shows how the Chinese provided finance, training and weapons to the Vietminh, but how differences about strategy emerged, particularly when China became involved in the Korean War and the subsequent peace negotiations, when the need to placate the United States and to prevent US military involvement in Southeast Asia became a key concern for the Chinese"--Provided by publisher